What are community studies? - Crow, Graham (Bloomsbury, 2018)
In the age of globalization and the changing welfare state, community relations are now more important than ever. 'What are Community Studies?' gives an overview of the community studies field, with particular focus on the research methods used, and how they have evolved in recent years. Defining the key terms in the field, it outlines the history of the methods used in community studies and uses examples and case studies to illuminate the theory. This book captures the organization of modern community life and shows how current researchers are working with broader and more imaginative definitions of community. Responding to criticisms of the field, 'What are Community Studies?' challenges our traditional notions of communities and how they are analysed.
Keywords: Stadtforschung; Stadtsoziologie; Gemeindesoziologie; Soziographie; Forschungsmethode; Lehrbuch; Begriffsbestimmung; Ethnographie